Songs of the Unsung : The Musical and Social Journey of Horace Tapscott - Tapscott, Horace (Book collections on Project MUSE., 2001)
Songs of the Unsung also includes Tapscott's vivid descriptions of the Watts neighborhood insurrection of 1965 and the L.A. upheavals of 1992, his interactions with both the Black Panthers and the L.A.P.D., his involvement in Motown's West Coast scene, the growth of his musical reputation abroad, and stories about many of his musician-activist friends, including Billy Higgins, Don Cherry, Buddy Collette, Arthur Blythe, Lawrence and Wilber Morris, Linda Hill, Elaine Brown, Stanley Crouch, and Sun Ra."--Jacket